(untitled) (New York, 2002)
This provocative narrative history dramatically departs from the standard "rise of the West" storyline that has driven world historiography for a century. A stellar group of historians paint a decidedly different modern world history, one in which the rise of the West was not predetermined and where global integration has manifested itself in fits and starts rather than as a smooth process over the last seven centuries. This fresh interpretation, driven by powerful ideas and colorful stories, promises to engage readers for decades to come.
Keywords: World history,History, Modern,Lịch sử thế giới,Lịch sử, Hiện đại